THE CRYSTAL STRUCTURE OF VERGASOVAITE CU3O[(MO,S)O4SO4], AND ITS RELATION TO SYNTHETIC CU3O[MOO4]2 - Berlepsch P.; Brugger J.; Armbrusten T.; Bykova E.Y.; Kartashov P.M. (My University, 1999)
The crystal structure of vergasovaite, Cu3O[(Mo,S)O4SO4], was determined from single-crystal X-ray data (space group Pnma, Z = 4, a = 7.421(2), b = 6.754(3), c = 13.624(5) Å) and refined to R1 = 3.99 %. The new mineral is isostructural with synthetic Cu3O[MoO4]2 but exhibits a highly unusual substitution of S6+ (ionic radius 0.12 Å) for Mo6+ (ionic radius 0.41 Å) in tetrahedral coordination. The synthetic and the natural structures are both characterized by edge-sharing zigzag chains of Jahn-Teller distorted Cu2+O6 octahedra with attached Cu2+ in five-fold pyramidal coordination (4+1). The strongly distorted Cu ribbons are connected by S6+ and Mo6+ bearing tetrahedra to form a three-dimensional framework. It is assumed that the structural strain due to the unusual S6+ ⇆ Mo6+ substitution is balanced by development of a different type of Jahn-Teller distortion compared to the synthetic end-member variety. The substitutional disorder of S and Mo in the mineral structure leads to strong static disorder in the entire structure as revealed by relatively high atomic displacement parameters for all atoms. It is suggested that an end-member of the type Cu3O[SO4]2 may not be stable due to the restricted flexibility of the square pyramidal coordination of Cu2+.